The Potency of Google Sites to Enhance Students Performance in Research Skills - Sagita, Sylva; Rahmat, Adi; Priyandoko, Didik; Sriyati, Siti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
This study aimed to determine high school students' perceptions of using Google Sites while improving research skills. How do students feel about using Google Sites for research learning regarding utility, ease of use, attitude, and intention to use? This article takes the initiative to explore the potential of the Google site to help students develop and retain research skills in planning, preparing, and writing research methods among senior high school students, especially related to finding information skills. The research used a descriptive qualitative approach, and the research subjects were 125 students of class XI and three Biology teachers who carried out research-based learning activities. In this study, a questionnaire survey was employed using a 5-point Likert scale, including perceived usefulness, perceived ease of use, attitude, and intention to use. The survey is in a Google form and shared via WhatsApp. According to the results of the study, Google Sites helped improve the abilities of students in research skills, especially in finding information from reliable sources. The collaboration between teachers and students in exploring this user-friendly platform fosters an environment of enthusiasm and confidence, paving the way for an enriched educational journey empowered by technology